2019
DOI: 10.1136/bmjopen-2018-028467
|View full text |Cite
|
Sign up to set email alerts
|

Cross-sectional study about the use of telemedicine for type 2 diabetes mellitus management in Spain: patient’s perspective. The EnREDa2 Study

Abstract: ObjectivesThe usefulness of telemedicine (TM) in type 2 diabetes mellitus (T2DM) has been discussed in recent years. The aim of this study is to describe patients’ perceptions about TM and to identify preferences on TM resources, in Spain.DesignAn observational, cross-sectional study was conducted using a structured questionnaire.Participants1036 patients with T2DM accepted to participate in the study (response rate: 68%).ResultsBlood glucose values were recorded by 85.9% of the patients while data such as lif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
34
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(36 citation statements)
references
References 39 publications
1
34
0
1
Order By: Relevance
“…As expected, TM also proved cost-effective from the health and societal perspectives [21,22], thanks to lower direct (clinical) and indirect (travel and work loss) costs. In general, TM should help pave the way to effective, efficient and patient-centered health care in the long run [3,15], facilitating and speeding up the interaction between patients and health professionals [21].…”
Section: Telemedicinesupporting
confidence: 71%
See 1 more Smart Citation
“…As expected, TM also proved cost-effective from the health and societal perspectives [21,22], thanks to lower direct (clinical) and indirect (travel and work loss) costs. In general, TM should help pave the way to effective, efficient and patient-centered health care in the long run [3,15], facilitating and speeding up the interaction between patients and health professionals [21].…”
Section: Telemedicinesupporting
confidence: 71%
“…Several studies have shown that TM is not inferior to traditional consultations in terms of clinical efficacy and quality of life, especially for chronic diseases which require periodic check-ups [18][19][20][21][22]. The most paradigmatic example is diabetes-probably not by chance the very first pathology to which the concept of patient empowerment was applied [23]-due to the crucial importance of lifestyle and thus the major role played by patients in the management of their own health.…”
Section: Telemedicinementioning
confidence: 99%
“… Face-to-face information was preferred as patients felt that it was more personal. Rodriguez-Fortúnez et al, 2019 (Spain) 24 Questionnaire Urban T2D elderly recruited from primary care Age: 60.3 years Diabetes duration: ≥1 year Telemedicine 70.5% patients were satisfied with the use of TM. They perceived that TM was able to reduce healthcare resource use including visits to the healthcare professionals, emergency room, and pharmacy, and time per visit.…”
Section: Methodsmentioning
confidence: 99%
“…Several studies have shown that TM is at least as good as traditional consultations in terms of efficacy and quality of life, especially for frequent and rare chronic diseases that require periodic check-ups and visits to hospitals [ 12 , 13 ]. The most paradigmatic example is diabetes, probably not by chance the very first illness to which the concept of patient empowerment was applied [ 14 ], owing to the crucial importance of lifestyle and thus the major role played by patients to manage their own health.…”
Section: State Of Art Of Telemedicinementioning
confidence: 99%
“…The most paradigmatic example is diabetes, probably not by chance the very first illness to which the concept of patient empowerment was applied [ 14 ], owing to the crucial importance of lifestyle and thus the major role played by patients to manage their own health. Not surprisingly, TM also resulted to be cost-effective from both health and societal perspectives [ 12 , 13 ], thanks to lower direct (clinical) and indirect (travel and work loss) costs.…”
Section: State Of Art Of Telemedicinementioning
confidence: 99%